Dichlorido[3-methoxymethyl-4-phenyl-5-(2-pyridyl)-4H-1,2,4-triazole-κ(2) N (1),N (5)]copper(II) - Cao, Shouping (International Union of Crystallography, 2011)
In the title complex, [CuCl(2)(C(15)H(14)N(4)O)], the Cu(II) atom possesses a highly distorted square-planar geometry with N—Cu—N and Cl—Cu—Cl angles of 79.86 (8) and 98.65 (3)°, respectively, while the Cl—Cu—N angles fall into two distinct groups with values of 95.26 (6), 98.75 (6), 150.56 (6) and 152.04 (6)°. The pyridyl ring is twisted by 9.4 (2)° with respect to the triazole ring, which is oriented at approximately right angles [84.66 (8)°] with respect to the phenyl ring.